The Translation Techniques of Anger Expressive Utterances in The Novel The Hate U Give (2017) by Angie Thomas - Meisha Rahmania; Havid Ardi (SPHOTA: Jurnal Linguistik dan Sastra, 2023)
This research was conducted to analyze the translation techniques of anger-expressive utterances found in the Novel The Hate U Give by Angie Thomas, translated into Indonesia. The purpose of the research was to study anger expressions and classify the translation techniques of anger used by the translator in The Hate U Give Novel and its translation. The data were gathered from reading the novel. There are 182 utterances that fall into the category of "expressions of anger" found in the novel.  From the result of data analysis, there were eleven types of translation techniques used by the translator in translated anger utterances found in the Novel, there were borrowing with 9 data, compensation with 9 data, transposition with 8 data, modulation with 12 data, amplification with 21 data, adaptation with 39 data, established equivalent with 61 data, generalization with 1 data, reduction with 11 data, variation with 2 data, and one technique that not include in Molina and Albir theory’s called neutralization with 9 data. Establish Equivalent was the most dominant translation technique.